Electrochemical low-frequency impedance spectroscopy algorithm for diagnostics of PEM fuel cell degradation. (6th January 2020) - Halvorsen, Ivar J.; Pivac, Ivan; Bezmalinović, Dario; Barbir, Frano; Zenith, Federico
Abstract: Prognostics and health management for fuel cells in real-world applications are important for optimization of lifetime and operation. A parameter that has been shown to indicate the state of ageing is the low-frequency intercept with the real axis of the Nyquist diagram in a fuel cell's impedance spectrum. This article presents a method for direct identification of this parameter, without the need to carry out a full electrochemical impedance spectroscopy, and with an algorithm that can be realized within a typical fuel-cell control system. The proposed method is based on relay excitation feedback, a proven solution from controller tuning.